Differences in late adolescent psychopathology among youth with histories of co-occurring abuse and neglect experiences. (October 2021) - Villodas, Miguel T.; Morelli, Nicholas M.; Hong, Kajung; Duong, Jacqueline; Evans, Meghan C.; Elson, Damian; Rose, Emma; Picci, Giorgia; Fishbein, Diana
Abstract: Background: Knowledge about the impacts of child abuse and neglect (CAN) experiences on late adolescent psychopathology has been limited by a failure to consider the frequent co-occurrence of CAN types and potential unique impacts of specific combinations. Objective: Using person-centered analyses, we aimed to identify unobserved groups of youth with similar patterns of lifetime CAN experiences before age 16 and differences in psychopathology symptom counts between groups two years later. Participants and setting: Participants were 919 adolescent-caregiver dyads (56% female; 56% Black, 7% Latina/o, 13% mixed/other). Methods: Prospective, multi-informant data, including child protective services records and caregiver and youth reports were collected, and youth completed a diagnostic interview at age 18. Results: Latent Class Analyses classified adolescents into four distinct groups based on patterns of physical neglect, supervisory neglect, and physical, sexual, and psychological abuse: "Low-Risk" (37%), "Neglect" (19%), "Abuse" (11%), and "Multi-type CAN" (33%). The Multi-type CAN class had significantly more major depressive, generalized anxiety, and nicotine use symptoms than the Low-Risk class, and more post-traumatic stress, antisocial personality, and illicit substance use symptoms, than Low-Risk and Neglect classes. The Abuse class had significantly more generalized anxiety and attention deficit/hyperactivity symptoms than the Low-Risk class, and more major depressive, antisocial personality, and illicit substance use symptoms, than Low-Risk and Neglect classes. The Neglect class did not have elevated psychopathology symptoms. Conclusion: Findings highlight important differences in the associations between lifetime CAN experience patterns and psychopathology. Researchers should explore mechanisms underlying psychopathology that are impacted by different CAN experience patterns.